A rare presentation of Salmonella Paratyphi B associated enteric fever and liver abscess: A case report and brief review (Indian Journal of Case Reports, 2019)
A pyogenic liver abscess (PLA) is a rare complication of enteric fever and is a potentially life-threatening condition. Here, we report a case of PLA secondary to enteric fever caused by Salmonella Paratyphi B in a 60-year-old male with diabetes mellitus and chronic alcoholism, who presented with fever, jaundice and abdominal pain. An ultrasound of the abdomen revealed a large abscess involving the left lobe of the liver with air-fluid level. Pus aspirated from the liver abscess yielded growth of Salmonella Paratyphi B which was susceptible to most of the commonly tested antibiotics. A Widal test performed also showed significant titers for Salmonella Paratyphi B. Percutaneous aspiration along with appropriate intravenous antibiotics resulted in a favourable clinical outcome in this patient.